Comparative proteomics profile of osteoblasts cultured on dissimilar hydroxyapatite biomaterials : an iTRAQ-coupled 2-D LC-MS/MS analysis - Khor, Khiam Aik (2012)
Hydroxyapatite (HA) and its derived bioceramic materials have been widely used for skeletal implants and/or bone repair scaffolds. It has been reported that carbon nanotube (CNT) is able to enhance the brittle ceramic matrix without detrimental to the bioactivity. However, interaction between osteoblasts and these bioceramics, as well as the underlying mechanism of osteoblast proliferation on these bioceramic surfaces remain to be determined. Using iTRAQ-coupled 2-D LC-MS/MS analysis, we report the first comparative proteomics profiling of human osteoblast cells cultured on plane HA and CNT reinforced HA, respectively. Cytoskeletal proteins, metabolic enzymes, signaling, and cell growth proteins previous associated with cell adhesion and proliferation were found to be differentially expressed on these two surfaces. The level of these proteins was generally higher in cells adhered to HA surface, indicating a higher level of cellular proliferation in these cells. The significance of these findings was further assessed by Western blot analysis. The differential protein profile in HA and CNT strengthened HA established in our study should be valuable for future design of biocompatible ceramics.